Pertimbangan Hakim dalam Menetapkan Pemberian Nafkah Istri dan Anak Setelah Perceraian di Pengadilan Agama Kabupaten Malang (Studi Kasus Putusan Nomor 7177/Pdt.G/2021/PA.Kab.Mlg) - iing randita budianti (Fakultas Hukum Universitas Islam Malang, 2022)
ABSTRACTDivorce means breaking up of a marital relationship. Divorce can only be carried out before the court concerned. Judges have the authority to decide divorce cases, including maintenance after divorce. For a wife who filed for divorce is said to be the same as daring to fight her husband so that her rights fall. Then what about the divorced wife? Are the rights also lost? Some divorce cases where the wife is divorced by the husband, sometimes they cannot maintain their rights as a divorced wife. Based on the provisions of Article 41 letter (c) of Law Number 1 of 1974, the judge can oblige the ex-husband to provide living expenses and or determine an obligation for the ex-wife. This article is the legal basis for the judge because his position can decide more than what is demanded, even though this is not demanded by the parties. The author uses a type of empirical juridical research with a sociological approach, aiming for the author to gain empirical legal experience by going directly to see the object, namely the consideration of the Panel of Judges in the decision of the case for the provision of a wife's livelihood at the Religious Court of Malang Regency. The result of the research obtained by the author is that the judge determines the alimony even though the wife does not demand it in accordance with the provisions of PERMA number 3 of 2017 concerning Guidelines for Adjudicating Women Facing the Law to protect the rights of the wife and children in her care after divorce. Taking into account the sense of justice and propriety by exploring the facts of the husband's economic capacity and the facts of the basic needs of his wife and/or children. Where the implementation of this provision of maintenance must be given first before the pledge is made, if the ex-husband does not carry out the decision, the case will be considered Non-Ex.Key Word : Divorce, Livelihood, Ex-officio Rights, PERMA No. 3 Year 2017 ABSTRAK Perceraian artinya putusnya sebuah hubungan perkawinan. Perceraian hanya dapat dilaksanakan didepan sidang pengadilan yang bersangkutan. Hakim memiliki kewenangan dalam memutuskan perkara perceraian termasuk juga nafkah setelah perceraian. Bagi istri yang mengajukan perceraian dikatakan sama dengan berani melawan suami sehingga haknya gugur. Lalu bagaimana bagi istri yang diceraikan? Apakah haknya juga gugur? Beberapa kasus perceraian dimana istri diceraikan oleh suami, terkadang tidak dapat mempertahankan haknya sebagai istri yang diceraikan. Berdasarkan ketentuan Pasal 41 huruf (c) UU nomor 1 tahun 1974, hakim dapat mewajibkan kepada bekas suami untuk memberi biaya penghidupan dan atau menentukan sesuatu kewajiban bagi bekas istri. Pasal ini merupakan dasar hukum hakim karena jabatannya dapat memutus lebih dari yang dituntut, sekalipun hal tersebut tidak dituntut oleh para pihak. Penulis menggunakan jenis penelitian yuridis empiris dengan pendekatan secara sosiologis, bertujuan agar penulis mendapatkan pengalaman hukum secara empiris dengan jalan terjun melihat langsung obyeknya yaitu pertimbangan Majelis Hakim dalam putusan perkara pemberiann nafkah istri di Pengadilan Agama Kabupaten Malang. Hasil penelitian yang diperoleh oleh penulis adalah Hakim menetapkan nafkah tersebut meskipun istri tidak menuntut sesuai dengan ketentuan PERMA nomor 3 tahun 2017 tetang Pedoman Mengadili Perkara Perempuan Berhadapan Dengan Hukum untuk melindungi hak istri dan anak yang ada dalam pemeliharaannya setelah perceraian. Dengan mempertimbangkan rasa keadilan dan kepatutan dengan menggali fakta kemampuan ekonomi suami dan fakta kebutuhan dasar hidup isteri dan/atau anak. Dimana pelaksanaan pemberian nafkah ini wajib diberikan terlebih dahulu sebelum ikrar diucapkan, bila bekas suami tidak melaksanakan putusan tersebut maka perkaranya akan dianggap NonEx. Kata Kunci : Perceraian, Nafkah, Hak Ex-officio, PERMA No 3 Tahun 2017.